Elite Engineering Education Programme in Tomsk Polytechnic University - the way to attract talented students into Engineering; Global Engineering Education Conference (EDUCON) - Chuchalin A. I. Alexander Ivanovich; Soloviev M. A. Mikhail Aleksandrovich; Zamyatina O. M. Oksana Mikhailovna; Mozgaleva P. I. Polina Igorevna (2013, 2013)
Title screen